An alternative method to evaluate the surface free energy of mineral fillers based on the generalized Washburn equation. (20th January 2020) - Zhang, Derun; Luo, Rong
Highlights: Model liquid wicking into capillaries of mineral fillers using generalized Washburn equation. Condition mineral fillers by saturated reference liquid vapors to form a duplex liquid film. Determine resultant effective capillary radius by conducting column wicking test on conditioned mineral fillers. Calculate surface free energy components of mineral fillers based on GvOC model. Evaluate accuracy of measured filler surface free energy by two reference methods. Abstract: This paper presents a new method to measure surface free energy of the mineral fillers. This method takes the generalized Washburn equation as theoretical basis. First, the mineral fillers are conditioned to form a duplex liquid film by saturated reference liquid vapors. The resultant effective capillary radius of the mineral fillers is then measured through the column wicking test of the conditioned mineral fillers using the reference liquid as test probe. After that, three independent liquids are selected to measure their spreading pressures on the mineral fillers based on their column wicking test results along with the measured resultant effective capillary radius. Finally, an equation set based on the Good-van Oss-Chaudhury model is established to compute the surface free energy of the mineral fillers. The newly developed method has been successfully applied to measure the surface free energy for four different types of mineral fillers. Distribution of the three surface energy components and range of the total surface free energy of the selected mineral fillers have been found to be consistent with those reported in literature for the particle aggregates with similar mineralogical composition. Besides, insignificant variation has been identified in each surface energy component of the mineral fillers measured from the new method and from the two references methods. In these regards, this new method can be used as an alternative for accurately measuring the surface free energy of the mineral fillers with simple test technique and high efficiency.